CdS/kaolinite composite prepared by chemical immersion method photocatalytic performance - Li Xue; Sun Zhiming; Li Chunquan; Zheng Shuilin (矿业科学学报, 2017)
In order to solve the problems of easy agglomeration and deactivation of CdS, and enhance the utilization of natural minerals, water washed kaolinite as a carrier, cadmium acetate and sodium sulfide as precursors,a novel visible light responding CdS/kaolinite composite photocatalytic material was prepared through the impregnation method.The optical properties of the obtained composites and visible light photocatalytic activity of different catalysts were characterized by X-ray diffraction (XRD),field emission scanning electron microscope (FE-SEM), transmission electron microscope (TEM), N2 adsorption-desorption analysis and UV-visible diffused reflectance spectroscopy (UV-vis). The CdS nanoparticles were firmly coating and effective dispersion on the lamellar structure of kaolinite, which could effectively restrain the recombination of photogenerated-carriers,improve optical corrosion properties of CdS photocatalytic materials and then further improve the photocatalytic efficiency.